2018
DOI: 10.1038/s41467-018-04068-0
|View full text |Cite
|
Sign up to set email alerts
|

Formation and radiative forcing of contrail cirrus

Abstract: Aircraft-produced contrail cirrus clouds contribute to anthropogenic climate change. Observational data sets and modelling approaches have become available that clarify formation pathways close to the source aircraft and lead to estimates of the global distribution of their microphysical and optical properties. While contrail cirrus enhance the impact of natural clouds on climate, uncertainties remain regarding their properties and lifecycle. Progress in representing aircraft emissions, contrail cirrus and nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
274
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 253 publications
(280 citation statements)
references
References 151 publications
(195 reference statements)
2
274
0
4
Order By: Relevance
“…Other climate agents directly emitted or affected by aircraft also contribute to the aviation total RF of climate on shorter time scales. This is in particular the case for aircraft NO x emissions affecting tropospheric ozone and the methane lifetime, emissions or formation of particles (black carbon, sulphates, nitrates) and, more importantly, formation of linear contrails and induced cloudiness (Karcher 2018). The aviation CO 2 RF of climate is estimated to represent 36%-51% of this total forcing including short-term climate forcers (Lee et al 2009, Grewe et al 2017, Karcher 2018.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other climate agents directly emitted or affected by aircraft also contribute to the aviation total RF of climate on shorter time scales. This is in particular the case for aircraft NO x emissions affecting tropospheric ozone and the methane lifetime, emissions or formation of particles (black carbon, sulphates, nitrates) and, more importantly, formation of linear contrails and induced cloudiness (Karcher 2018). The aviation CO 2 RF of climate is estimated to represent 36%-51% of this total forcing including short-term climate forcers (Lee et al 2009, Grewe et al 2017, Karcher 2018.…”
Section: Discussionmentioning
confidence: 99%
“…This is in particular the case for aircraft NO x emissions affecting tropospheric ozone and the methane lifetime, emissions or formation of particles (black carbon, sulphates, nitrates) and, more importantly, formation of linear contrails and induced cloudiness (Karcher 2018). The aviation CO 2 RF of climate is estimated to represent 36%-51% of this total forcing including short-term climate forcers (Lee et al 2009, Grewe et al 2017, Karcher 2018. These additional terms are subject to large uncertainties and will be analysed in forthcoming studies with the OSCAR compact carbon cycle-climate change model in order to account for the different lifetimes of the various climate agents involved or with the more complex LMDz-INCA chemistry-climate model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cirrus clouds evolving from aircraft contrails cause the largest contribution to aviation-induced radiative forcing (Burkhardt & Kärcher, 2011;Kärcher, 2018). However, its quantification is affected by significant uncertainties, which underlines the importance to perform appropriate measurements to better understand processes governing contrail formation and evolution (Heymsfield et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Fluid-dynamical models (Huebsch & Lewellen, 2006;Unterstrasser, 2016) and measurements Schumann et al, 2013) have shown that aircraft wake dynamics can have marked effects on contrail properties. This includes the possibility of ice particle losses during the descent of wake vortices Geophysical Research Letters 10.1029/2018GL079390 forcing ice particle sublimation due to adiabatic heating even if the ambient air surrounding the contrail is ice-supersaturated (Kärcher, 2018;Paoli & Shariff, 2016). Assessing contrail properties toward the end of the vortex phase is of particular interest, as they affect properties of evolving contrail cirrus over hours (Unterstrasser & Gierens, 2010).…”
Section: Introductionmentioning
confidence: 99%